2016
DOI: 10.1002/sia.5973
|View full text |Cite
|
Sign up to set email alerts
|

Surface spectroscopy and structural analysis of nanostructured multifunctional (Zn, Al) layered double hydroxides

Abstract: Two types of (Zn, Al) layered double hydroxide were prepared by a hydrothermal process at room temperature using Zn salt precursors on Al foils. The examined LDHs differ for the hosted anions in the interlamellar space, namely Cl À and NO 3 À . Scanning electron microscopy, X-ray photoelectron spectroscopy and ultraviolet photoemission spectroscopy have been used to characterize four types of the samples, representative of the two hosted anions (Cl À and NO 3 À ) and two times of growth (6 and 24 h). X-ray pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…As already explained, in the solvent, the CMC cluster dissociated to 2 Cs + and 1 [Mo 6 Cl i 8 Cl a 6 ] 2ions and the Cs + cation can be kept by the exchangeable anion adsorbed on the LDH or Cl-from CMC, which was removed through the washing step. The binding energies of Zn 2p and Al 2p are respectively assigned by the two peaks at 1022.3 eV (2p 3/2 ) and 1045.4 eV (2p 1/2 ) and a peak of 74.7 eV that agrees with a previous study[48]. The dodecyl sulfate component is confirmed by the appearance of the binding energy of the S2p at the peak of 169.1 eV.It is important to verify the difference in the binding energy of the Mo and Cl components in the Mo 6 cluster after intercalated into the LDH.…”
supporting
confidence: 90%
“…As already explained, in the solvent, the CMC cluster dissociated to 2 Cs + and 1 [Mo 6 Cl i 8 Cl a 6 ] 2ions and the Cs + cation can be kept by the exchangeable anion adsorbed on the LDH or Cl-from CMC, which was removed through the washing step. The binding energies of Zn 2p and Al 2p are respectively assigned by the two peaks at 1022.3 eV (2p 3/2 ) and 1045.4 eV (2p 1/2 ) and a peak of 74.7 eV that agrees with a previous study[48]. The dodecyl sulfate component is confirmed by the appearance of the binding energy of the S2p at the peak of 169.1 eV.It is important to verify the difference in the binding energy of the Mo and Cl components in the Mo 6 cluster after intercalated into the LDH.…”
supporting
confidence: 90%
“…In a previous work of Richetta et al [34] (Zn-Al) LDH nanostructures were grown on Al foils. A nutrient solution composed of a 1:1 ratio of zinc chloride ZnCl 2 and hexamethylenetetramine (C 6 H 12 N 4 ) at 5 mM concentration was employed for the hydrothermal growth of LDH.…”
Section: Co-precipitationmentioning
confidence: 99%
“…Those studies were mainly addressed applications of LDHs as anticorrosion coatings or functionalized electrodes for electrical batteries and capacitors. More recently, our group has demonstrated that controlled films can also be grown an aluminum thin films, which were previously sputtered or evaporated on any surface [33,107]. In this way, LDHs films made of lamellar-like nanoplatelets, can be grown selectively on specific areas, with submicrometric-level resolution (about ±0.5 m), by prepatterning the aluminum layer with conventional photolithographic techniques (Figure 3).…”
Section: Controlled Film Depositionmentioning
confidence: 99%